Hemodynamic Congestion at Hospital Discharge Predicts Rehospitalization during Short Term Follow Up in Acute Heart Failure Patients - Yoga Waranugraha; Mohammad Saifur Rohman; Setyasih Anjarwani (Jurnal Kardiologi Indonesia, 2019)
Background: Hemodynamic congestion is an increase in left ventricular diastolic pressure (LVEDP) without clinical symptoms and signs of congestion. Current acute heart failure (AHF) treatment goals only focused on improving clinical congestion. The purpose of this study was to investigate whether hemodynamic congestion measured by NT-proBNP level and ePCWP at hospital discharge could predict short term clinical outcomes in AHF patients. Method: This prospective cohort study was conducted at dr. Saiful Anwar General Hospital Malang from January to July 2018. All patients got AHF treatment according to the 2016 ESC guidelines for heart failure. All patients were discharged without symptoms and signs of clinical congestion. Hemodynamic congestion at hospital discharge was defined as failure of treatment during hospitalization to achieve a reduction in NT-proBNP level >30% and/or ePCWP at hospital discharge >16 mmHg. NT-proBNP level and ePCWP were measured at 0-12 hours after hospital admisssion and at hospital discharge. ePCWP was measured using echocardiography. The clinical outcomes assessed were AHF rehospitalization and cardiovascular mortality within 30 days after hospitral discharge. Subgroup analysis was performed to determine therapeutic regimens that are effective in improving hemodynamic congestion. Result: A total of 33 AHF patients were included in this study. 48% patients were discharged with hemodynamic congestion and 52% patients discharged without hemodynamic congestion. Patients with hemodynamic congestion at hospital discharge showed a higher rehospitalization within 30 days (8 [50%] vs 1 [5.9%]; P = 0.007). Mortality within 30 days in both groups did not show a significant difference (2 [12.5%] vs 0 [0%]; P = 0.277). Treatment regiment of optimal dose of ACEi/ARB, Î²-blockers, and diuretics was associated with improvement of hemodynamic congestion (P = 0.026; r = 0.454), a decrease in NT-proBNP> 66% (P = 0.02; r = 0,574), and achievement of ePCWP <16 (P = 0,013; r = 0,493) at hospital discharge in HFrEF patients. Conclusion: This study showed that hemodynamic congestion assessed with NT-proBNP level and ePCWP at hospital discharge increased 30 day rehospitalization in AHF patients. In HFrEF, improvements in hemodynamic congestion can be achieved by giving the treatment regiment of optimal dose of ACEi/ARB, Î²-blockers, and diuretics. Keyword: Acute heart failure, hemodynamic congestion, NT-proBNP, ePCWP